ANALYSIS OF USER SATISFACTION LEVEL IN F-LEARN USING EUCS METHOD - Pali'pangan, Prihart Julian; Pakereng, Magdalena A. Ineke (Universitas Methodist Indonesia, 2023)
The changes in various aspects of life have led to the rapid development of information technology, enabling it to encompass all fields of knowledge in the education world and support the teaching and learning process. E-Learning is an integrated system developed through a holistic approach to ensure the effectiveness and interconnectedness of learning. It directly connects learners with relevant learning-teaching resources, facilitating active interaction and in-depth exploration. Flexible-Learning (F-Learn) is a distance learning platform at Satya Wacana Christian University (UKSW) that supports academic activities. The End User Computing Satisfaction (EUCS) method is used as an evaluation tool to measure user satisfaction with the application system by comparing their expectations with their actual user experience. The research aims to measure and evaluate students' satisfaction level with the use of F-Learn as a benchmark for the quality of services provided. Based on the conducted analysis, the content rating score is 3.9775, accuracy is 3.485, format is 3.31, usability is 3.82, and timeliness is 4.115.